Fiscal benefits of the primary sector, agriculture, catle raising , forestry and fisheries - Yepiz Solís, Brenda Lilian (Posgrados de la División de Ciencias Económica Administrativas, 2021)
The primary sector, which includes agricultural, livestock, fishing, and forestry activities, has enormous importance in the development of the economy. Considering the above for several years, legislators and tax authorities have granted various tax benefits to this sector (Pérez, 2016). The information that you will find in the first place, the problem that led you to choose the subject, is that in this sector it is mostly located in areas far from the cities and, derived from that, they have very little administrative capacity and structure to comply with their tax obligations ; The objective is to identify the benefits and incentives applicable to companies, both physical and legal persons when taxing this regime for the determination of the tax burden, qualitative descriptive methodology, we will know the requirements and the obligations it entails, then it focuses on knowing the benefits What are the administrative facilities and fiscal incentives that can be obtained, it can be observed in the research that there are benefits and incentives in terms of income tax, social security and also on the acquisition of diesel; all this with the intention of exposing the benefits and determining if it is convenient mainly in economic matters.